The Role of Preoperative Computed Tomography on the Quality of Reduction and Outcomes in Intertrochanteric Fracture: A Controlled Trial. (12th February 2021) - Ma, Tao; Hao, Lin-Jie; Wen, Peng-Fei; Wang, Ya-Kang; Wang, Hu; Zhang, Bin-Fei; Zhang, Yu-Min
Abstract : Purpose . The study is aimed at assessing the role of preoperative computerised tomography (CT) examination in the quality of reduction and outcomes in elderly patients with intertrochanteric fracture. Methods . The elderly patients with an intertrochanteric fracture who were treated with proximal femoral nail antirotation were included. The patients were divided into the CT group and the no-CT group according to the presence of preoperative CT examination. Patients' baseline characteristics, quality of reduction, and function were recorded at follow-up. Functional outcomes were evaluated using the Harris hip scores (HHS). Results . Totally, the study included 182 patients with intertrochanteric fractures, with 85 in the CT group and 97 in the no-CT group, admitted between January 2018 and June 2019. There was no difference in the quality of reduction, HHS, the fracture healing, or postoperative complications between the CT group and the no-CT group. However, the CT group experienced the shorter mean operative time and blood transfusion, compared to the no-CT group. Conclusions . The preoperative CT examination seems to be excessive for elderly patients with an intertrochanteric fracture.